Assessment of knowledge, attitude and practice regarding nutritional care and sarcopenia in oncology: a cross-sectional pilot survey - Basu, Debasis; Das, Sudeep; Banerjee, Tanmay; Mohapatra, Prabrajya Narayan; Singh, Nidhi; Ghosh, Soutri (International Journal of Research in Medical Sciences, 2026)
Background: Malnutrition and sarcopenia are highly prevalent in cancer patients and are associated with poor clinical outcomes. Despite increasing awareness, their assessment and management remain inconsistent in routine oncology practice. To assess the knowledge, attitude and practice (KAP) of healthcare professionals regarding nutritional care and sarcopenia in oncology settings. Methods: A cross-sectional survey was conducted among 18 clinicians using a structured questionnaire covering knowledge, attitude and practice domains. Responses were analyzed using descriptive statistics and domain-wise scores were calculated. Results: The findings demonstrated moderate knowledge levels, with variability in understanding of sarcopenia definitions, diagnostic tools and biomarkers. Attitude toward nutrition was highly positive, with most participants acknowledging the importance of early nutritional intervention and routine screening. However, clinical practice lagged behind, with low adoption of structured screening tools such as SARC-F and handgrip strength, limited routine nutritional assessment and inconsistent tracking of body composition. Conclusions: Despite favorable attitudes, a significant gap exists between knowledge and implementation of nutritional care in oncology. Targeted education and integration of structured screening tools are essential to improve clinical outcomes.